Maslahah On Siri Marriage Family Cards In Peraturan Menteri Dalam Negeri Number 108 Of 2019 - Firdaus, Muhammad Isro; Rahmat Hakim, Budi; Mariani, Mariani (Sharia Journal and Education Center Publishing, 2023)
Abstract Permendagri No. 108/2019 Article 10 regulates the issuance of Family Cards for siri marriage couples. This policy provides benefits in the form of a statement of relationship status in the form of family ties consisting of the head of the family, wife and children. However, the issuance of this Family Card has a mudharat, namely that it will increase the number of siri marriages because it weakens the provisions of marriage registration regulated in Article 2 paragraph 2 of Law Number 1 Year 1974 concerning Marriage. This research examines the Family Card for siri marriage from a Maslahah perspective. Does this siri marriage family card bring maslahah or even bring mudharat. This research aims to provide information and knowledge about Maslahah on siri marriage family cards. The method used in this research is a normative method with a literature study that refers to the literature as the basis for analyzing the topic that is the object of research. To obtain the data needed in the research, the author searches for legal materials, conducted by reading, viewing, listening and searching through internet media. The findings in this study indicate that the Family Card of nikah siri contains maslahah at the dharuriyat level considering so many benefits, basically all of which are in the context of maintaining the objectives of Islamic law, namely maintaining religion, maintaining the soul, maintaining the mind, maintaining offspring, and maintaining property. Abstrak Permendagri Nomor 108 Tahun 2019 Pasal 10 mengatur penerbitan Kartu Keluarga bagi pasangan nikah siri. Kebijakan ini memberikan kemaslahatan berupa adanya keterangan status hubungan dalam bentuk ikatan keluarga yang terdiri dari kepala keluarga, istri dan anak. Akan tetapi, penerbitan Kartu Keluarga ini memiliki mudharat yakni akan meningkatkan angka pernikahan siri sebab memperlemah ketentuan pencatatan perkawinan yang diatur dalam Pasal 2 ayat 2 Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. Penelitian ini mengkaji Kartu Keluarga nikah siri ditinjau dari perspektif Maslahah. Apakah Kartu Keluarga nikah siri ini mendatangkan maslahah atau malah mendatangkan mudharat. Penelitian ini bertujuan untuk memberikan informasi dan pengetahun tentang Maslahah pada Kartu Keluarga nikah siri. Metode yang digunakan dalam penelitian ini adalah metode normatif dengan studi pustaka yang mengacu kepada literature-literatur sebagai basis analisis terhadap topik yang dijadikan obyek penelitian. Untuk memperoleh data yang diperlukan dalam penelitian maka penulis melakukan penelusuran bahan-bahan hukum, dilakukan dengan membaca, melihat, mendengarkan dan menelusuri melalui media internet. Temuan dalam penelitian ini menunjukkan bahwa Kartu Keluarga nikah siri mengandung maslahah pada tingkatan dharuriyat mengingat begitu banyak manfaat yang pada dasarnya kesemuanya itu adalah dalam rangka memelihara tujuan hukum Islam yakni memelihara agama, memelihara jiwa, memelihara akal, memelihara keturunan, dan memelihara harta. Kata kunci: Maslahah, Kartu Keluarga nikah siri, Permendagri Nomor 10 Tahun 2019.